"Keeping us on our toes": a review of what clinicians need to know about vancomycin-variable Enterococcus - Marten R. Hawkins; Natalia Medvedeva; Hannah Wang; Niaz Banaei; Marisa K. Holubar (Cambridge University Press, 2024)
Enterococcus faecium is a difficult-to-treat gram positive organism with increasing rates of resistance to vancomycin which is commonly mediated through the vanA gene cluster. There have been international reports of E. faecium isolates that are genotypically positive for vanA but phenotypically vancomycin-susceptible. These isolates, commonly called vancomycin-variable enterococci (VVE), can convert to phenotypic vancomycin resistance upon exposure to vancomycin. Multiple mechanisms for this genotypic-phenotypic mismatch have been reported and most commonly involve the regulatory components of the vanA gene cluster. VVE are challenging to identify unless microbiology labs routinely implement both genotypic and phenotypic screening methods. VVE has been associated with outbreaks and has become a prevalent pathogen in several countries. In this review, we summarize the mechanisms, microbiology and epidemiology of VVE. Clinicians must remain vigilant for VVE as diagnosis can be challenging and treatment failure on vancomycin is possible.